Proposta de aerador para tanques de pequeno porte na aquicultura: perspectivas para a região de Pedro Afonso, Tocantins - Matos, Domingos Ney Vieira de (2023)
Fish farming has emerged as a prominent activity in the municipality of Pedro Afonso, Tocantins, Brazil. The region, characterized by rivers, lakes and dams, offers favorable conditions for the development of this practice, given the availability of water resources. In addition to its economic potential, fish farming in Pedro Afonso plays a crucial role in local food security, meeting the demand for animal protein in the population's diet. However, depending on the region's climatic characteristics, high water temperatures can be a barrier to the development and expansion of this sector. In this context, a vital component is the aerator, a device that promotes circulation and adequate oxygenation of water, establishing an environment conducive to fish growth and reproduction. The introduction of air into the water, carried out using specific pumps or aerators, plays a fundamental role in oxygenation. The aerator, by avoiding low concentrations of dissolved oxygen, preserves the vitality of the fish and, additionally, contributes to the removal of toxic gases, such as carbon dioxide, and harmful residues, such as ammonia and nitrates. However, the high energy consumption associated with this equipment represents a challenge, impacting the operational costs of fish farming. This dilemma is especially noticeable in small businesses, where high electricity costs can affect producers' profitability. Therefore, the present study focuses on offering an alternative to an aerator aimed at water oxygenation as a critical factor for the success of fish farming. To this end, the study analyzes the economic viability of implementing a refrigerator compressor as an alternative to conventional oxygenation methods in fish farming activities. Through a literature review, the operating principles of the refrigerator compressor, its benefits and its applicability in this activity will be explored. A comparative analysis of the dissolved oxygen incorporation efficiency will be conducted using the SAE (Standard Aeration Efficiency) and SOTR (Standard Oxygen Transfer Rate) parameters between the refrigerator compressor and conventional methods, as supported by the literature. Furthermore, the economic aspects associated with the adoption of this equipment were investigated, considering its potential impact on the operational costs of fish farming in Pedro Afonso. Ultimately, this study seeks to provide a comprehensive perspective on the feasibility of adopting refrigerator compressors in aquaculture to improve oxygenation in fish farming systems. As results, it is expected to provide support for decisions that consider both the environmental benefits and the economic aspects inherent to this innovation in the practice of fish farming in Pedro Afonso, Tocantins.